Opening the window to the children’s mind: the superior efficacy of open-ended physical games in the development of attention and socio-emotional skills - Lyu, Shanshan; Zhang, Weixiao (Frontiers in Psychology, 2025)
BackgroundThe promotional effects of physical exercise on children’s attention and social–emotional skills have been widely confirmed. However, the advantages of open physical games in intervention effects still need further exploration. Therefore, this study discusses the intervention effects of open physical games on children’s attention and social–emotional skills.MethodsThis study adopted a quasi-experimental design. Two administrative classes were divided into the experimental group (15 boys and 16 girls) and the control group (16 boys and 15 girls) using the coin-toss method. The intervention intensity was moderate (60–69% of HRmax), lasting for 12 weeks, with 3 sessions per week, each lasting 40 min. Both groups focused on the teaching of fundamental motor skills (FMS). The experimental group was intervened with open physical games, while the control group was intervened with closed physical games. The Adolescent Attention Test was used to measure attention quality; the Children’s Social and Emotional Skills Scale was used to measure social–emotional skills; the Test of Gross Motor Development-Third Edition was used to measure locomotors and manipulative skills; and the Fundamental Movement Skill Development Test for Children Aged 3 to 10 was used to measure stability skills. Based on SPSS 25.0 and GraphPad Prism 8 software, statistical analysis was conducted using independent samples t-tests, χ2 tests, MANOVA, and Pearson partial correlation analysis.ResultsAfter the intervention, open physical games had a more positive effect on children’s attention distribution (F = 6.223, p = 0.022, η2 = 0.090). Open physical games had a more positive effect on children’s self-awareness (F = 11.027, p = 0.002, η2 = 0.165), others’ awareness (F = 10.315, p = 0.002, η2 = 0.156), collective awareness (F = 6.494, p = 0.014, η2 = 0.104), collective management (F = 12.108, p = 0.001, η2 = 0.178), and overall social–emotional skills (F = 38.453, p < 0.001, η2 = 0.407). Open physical games had a more positive effect on locomotors skills (F = 6.458, p = 0.014, η2 = 0.104), manipulative skills (F = 6.380, p = 0.014, η2 = 0.102), and overall FMS (F = 10.333, p = 0.002, η2 = 0.156). In addition, there is a certain degree of positive correlation between FMS, attention, and social–emotional skills (p < 0.05).ConclusionOpen physical games have superior effects on children’s attention, social–emotional skills, and FMS compared to closed physical games. This has guiding significance for subsequent physical education practices and the formulation of public health policies.